Internal Communication for Achieving Internal CSR Engagement - Hernandez, Cristobal (2012)
This dissertation addresses the topic of internal communication and its role for achieving engagement and involvement from the internal audience of organizations. The objectives of this dissertation are twofold. The first objective is to review the existing literature about this topic and set a parameter regarding which sub topics are involved in it. The second one is about developing a model of internal communication for achieving internal CSR engagement.